2013
DOI: 10.4103/0378-6323.104671
|View full text |Cite
|
Sign up to set email alerts
|

mRNA and DNA PCR tests in cutaneous tuberculosis

Abstract: The results of PCR tests in cutaneous tuberculosis should be interpreted in the light of clinical and histopathological findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Other studies have reported PCR positivity in CTB ranging from 5%-77%. [30][31][32][33][34] This variation in results and range is possible because of FFPE tissue being used for the extraction of tubercular DNA. Formalin fixation affects DNA retrieval by 2 main factors: the amount of formalin used and the duration of fixation, 35 which also affects TB-PCR results.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported PCR positivity in CTB ranging from 5%-77%. [30][31][32][33][34] This variation in results and range is possible because of FFPE tissue being used for the extraction of tubercular DNA. Formalin fixation affects DNA retrieval by 2 main factors: the amount of formalin used and the duration of fixation, 35 which also affects TB-PCR results.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this low sensitivity of TB-DNA and TB-RNA assay could be as follows: (1) NTM strains are not in the detection range; (2) the presence of PCR inhibitors; (3) insufficient mycobacteria load and nucleic acid material in some specimens which are possibly caused by the severity of the infection. For the TB-RNA assay, especially the RNA degradation (Suthar et al, 2013 ; Marangu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has a sensitivity ranging between 33% and 96% and specificity of 62.5% for pulmonary tuberculosis. 14 The TST is an useful adjunct in diagnosis of CTb, but it fails to distinguish active and past infections, and can even be negative in some forms of CTb, and in unvaccinated populations, the sensitivity increases to 97%. 6 Besides there is variation seen with the type of lesion, that is, TB chancre, miliary TB, and tuberculous orificialis often show negative TST results, whereas scrofuloderma and lupus vulgaris show strong TST positivity.…”
Section: Tuberculin Skin Testmentioning
confidence: 99%